Effect of Tinnitus Habituation Therapy on Auditory Abilities - Burle,Najlla Lopes de O. (2021)
Abstract Introduction Research with tinnitus patients presenting with hearing loss and normal hearing subjects have verified that tinnitus interferes with auditory processing. One treatment option for this symptom consists of tinnitus habituation therapy. Objective To determine the influence of tinnitus habituation therapy on auditory abilities, on the self-perception of tinnitus regarding loudness and discomfort, and its impact on the quality of life. Methods A quasi-experimental study was conducted with 19 individuals with tinnitus. Audiological tinnitus and auditory processing evaluations were performed. Subsequently, the volunteers underwent tinnitus habituation therapy for 6 months. Ultimately, all of the individuals were reevaluated. Results A statistically significant reduction in tinnitus self-perception was observed in relation to loudness, discomfort, and its impact on the quality of life (p = 0.001, 0.001, 0.023, respectively). However, the influence of tinnitus habituation therapy on auditory abilities was not verified. Conclusion Tinnitus habituation therapy was effective in reducing the self-perception of tinnitus loudness and discomfort, as well as the impact of the symptom on the quality of life. However, these factors did not improve the auditory processing skills in tinnitus patients.